Dari Pesantren Menuju Kancah Politik: Tumbuh Kembang Pesantren Giri Kedhaton Abad Ke 15-17 M - Miselan, Aina Ilmi Maziyya; Prasetya, Restu Dimas (Qurthuba: The Journal of History and Islamic Civilization, 2025)
This research, focus to discuss about Islamic Boarding School Of Giri Kedhaton that established by One Walisongo, Sunan Giri and this research, discuss about transformation from this Islamic Boarding School from Islamic Religion Instantion to Political Instantion. This research will discuss. From this research, we get: 1)Islamic Boarding School Of Giri Kedhaton established when Java at chaos time after Majapahit Game Of Throne, 2)one figure who spread Islam at Gresik is Sunan Giri who also build Islamic Boarding School Of Giri Kedhaton, 3)From educated his students at Giri Kedhaton, Sunan Giri used traditional method: Sorogan and Bandongan and also educated his students at lifeskill and preach, 4)Giri Kedhaton was transform from Islamic Religion Instantion to Islamic Political Instation at 16 TH Century, 5)at 16 TH Century, Giri Kedhaton attacked for many times by Kingdom Of Majapahit and tried defend his existension , 6)under Sunan Prapen, Giri Kedhaton achieve his golden age and active spread Islam to Bali, Lombok, Sulawesi, and Maluku, 7)after die of Sunan Prapen, Giri Kedhaton suffered retrogression until fall to VOC at 1679/1680 AD. 8)Giri Kedhaton, handled important position at 16 TH Century Java Political Map, because became legitimator for Demak and Pajang s kings. Keywords: Sunan Giri, Giri Kedhaton, Demak, Pesantren, Politic.